2014
DOI: 10.1007/s00167-014-2980-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined arthroscopic management of concurrent posterior and anterior ankle pathologies

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 40 publications
0
23
0
1
Order By: Relevance
“…We did not observe a higher rate of infections in our patients, which is in accordance with the data reported by other authors using this approach. 1,3,41 A study of a technique in which anterior ankle arthroscopy was performed first, followed by position switching from supine to prone, reported that the median time needed for position switching was 15 minutes. 28 However, patients were under general anesthesia, the leg was initially positioned in a holder with the hip flexed for 45 degrees, and with the use of noninvasive bandage distraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe a higher rate of infections in our patients, which is in accordance with the data reported by other authors using this approach. 1,3,41 A study of a technique in which anterior ankle arthroscopy was performed first, followed by position switching from supine to prone, reported that the median time needed for position switching was 15 minutes. 28 However, patients were under general anesthesia, the leg was initially positioned in a holder with the hip flexed for 45 degrees, and with the use of noninvasive bandage distraction.…”
Section: Discussionmentioning
confidence: 99%
“…21 It was at the final follow-up when patient’s satisfaction was evaluated using a 3-question survey, as reported by Abdelatif. 1…”
Section: Methodsmentioning
confidence: 99%
“…We start with the anterior arthroscopy in the supine position. After finishing the procedure, the patient is placed in the prone position for the two-portal hindfoot approach 12 14 56…”
Section: Current State Of the Artmentioning
confidence: 99%
“…In Europe and Asia, most surgeons use the dorsiflexion method, with a two-portal technique. Depending on the diagnosis, an anterior or posterior approach or a combined approach is chosen 56. Arthroscopy as a diagnostic tool has been abandoned for a variety of reasons.…”
Section: Current State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation